SMART E-COMMERCE UNTUK STRATEGI PEMASARAN GUNA PENINGKATAN PENJUALAN HASIL PERTANIAN (SiPeHtanI) - Pramadhana, Dian; Amalia, Dita Rizki; Ghozali, Ahmad Lubis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Indonesia is known as an agriculture-based country, where the majority of its population works as farmers. The agricultural sector in Indonesia significantly contributes to supporting the national economy. Indramayu Regency, located in West Java Province, is famous as a national rice production center due to its major role in national rice production. However, many farmers are still disadvantaged due to the lengthy agricultural product marketing chain, which makes the marketing system inefficient. Farmers are limited to selling their produce only to local traders at lower prices. This situation needs improvement so that the agricultural products of the Indramayu community can be better enjoyed by both consumers and farmers. This research aims to develop an agricultural product sales information system by creating an e-commerce website. An e-commerce system can be an option for farmers, serving as a means for promotion, communication, and information delivery, while also reducing the distribution chain in agricultural product marketing. The development of marketing channels for agricultural products can influence the demand for production, thus encouraging increased production among farmers. Additionally, the prices offered to buyers are relatively cheaper, which can increase the sales of agricultural products and provide greater benefits to farmers.